Effects of a combined technique and agility program on youth soccer players` skills - Zago, M.; Giuriola, M.; Sforza, C. (International Journal of Sports Science & Coaching, 2016)
High-intensity actions with high technical demands heavily influence soccer game outcomes. While performance factors have been traditionally trained separately, a program combining agility and technique training was proposed, structured on artificial constraints (tapes) creating spatiotemporal restrictions.